Нація як спільнота в соціологічній спадщині Володимира Старосольського - Ляшук, Людмила Леонідівна; Ляшук, Людмила Леонидовна; Liashuk, Liudmyla L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті обґрунтовано доцільність пошуку чинників, що вплинули на становлення націотворчої концепції В. Старосольського. Проаналізовано об’єктивні критерії нації, що слугують її складовими компонентами та характеризують націю як спільноту, яка твориться стихійною волею й араціональним типом поведінки. Останні реалізуються в прагненні побудувати державу через самоусвідомлення спільноти, яка, будучи новим суспільним об’єднанням, керується свідомою волею та сприяє реалізації інтересів нації. This article analyzes the factors nation creation process in a sociological legacy V. Starosolskу that reveals the essence of the nation by understanding it as a community. This enables determine basic factors of nations, main among which are: territory, race, culture and language. Reveal the dialectical relationship these signs is denotative in the fight for independence, thereby facilitating the emergence on the international scene a new social formation – state, which is the result of conscious action of the nation. Are the parallels to sociological achievements V. Antonovich, V. Lypynsky, and O. Bochkovsky and S. Rudnitsky, who offered their own concept of the nation.
Nation as Association in the Sociological Inheritance of Vladimir Starosolsky
Keywords: нація; спільнота; суспільство; держава; воля; nation; community; society; state; will